Opinions of the Ankara Special Provincial Administration Directors on the Transferring Process of the Public Libraries of Turkey to Local Authorities - Bülent Yılmaz; Derya Baklacı; Ömer Çetin; Vuslat Güler; Yelda Güneyoğlu; Dilek İskenderoğlu (Türk Kütüphaneciliği)
This study is carried out in order to reveal the local managers’ approaches about “transferring public libraries to local authorities” which has been intensely argued for  the last three-four years in Turkey. Within this frame, a poll was conducted on countyspecial provincial administration directors working in the counties of Ankara. According to the results of the poll dated June, 2010 which was conducted on totally 15 county directors, they state that they do not find themselves sufficient about shaping the public library services and do not want any change about connecting the public libraries to themselves and they think that an alteration regarding the transferring of the public libraries would not create a significant difference on the existing situation.